2023
DOI: 10.1007/s00383-023-05426-w
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic injection of bulking agents in pediatric vesicoureteral reflux: a narrative review of the literature

Abstract: In the last 20 years, endoscopic injection (EI) has affirmed as a valid alternative to open surgery for management of pediatric vesicoureteral reflux (VUR). This study aimed to investigate and discuss some debated aspects such as indications, bulking agents and comparison, techniques of injection and comparison, predictive factors of success, use in specific situations. EI is minimally invasive, well accepted by patients and families, with short learning curve and low-morbidity profile. It provides reflux reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…The cause of the early obstructions reported in the literature may be the physical obstruction caused by the injected material. 13 Rossini et al 14 reported that VUR in children can predispose patients to febrile UTIs. Repeated UTIs can lead to renal scarring, hypertension, and ultimately end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the early obstructions reported in the literature may be the physical obstruction caused by the injected material. 13 Rossini et al 14 reported that VUR in children can predispose patients to febrile UTIs. Repeated UTIs can lead to renal scarring, hypertension, and ultimately end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ендоскопічну технологію можна вважати певною мірою альтернативою традиційній уретероцистонео стомії (УЦНС) з урахуванням її доволі високої ефективності, мінімальної травматичності, можливості повторних втручань та швидкої післяопераційної реабілітації дітей. Наводяться дані про 76% ефективність ліквідації МСР після однократної ін'єкції та 98% -після двократної [2,4,7]. З удосконаленням методик ширше застосовується корекція навіть IV-V ступенів МСР із використанням різних об'ємоутворювальних речовин [1,5].…”
Section: вступunclassified
“…Thanks to its low invasiveness and morbidity, the cystoscopic injection of bulking agents has become a popular alternative for the treatment of VUR. 5 , 6 , 9–11 …”
Section: Introductionmentioning
confidence: 99%